Eupraxsophy: Sebuah Pandangan tentang Humanisme Sekular Menurut Paul Kurtz - Geroda Hayon, Heribertus (Fakultas Teologi, Universitas Sanata Dharma, 2023)
This article discusses the concept of humanism, especially in the context of secular humanism as advocated by Paul Kurtz. Humanism, as a movement that emerged during the Renaissance, emphasizes the importance of happiness, freedom, and human rights. Kurtz, a significant figure in secular humanism, articulates a worldview that focuses on courage, cognition, and compassion as fundamental virtues guiding human life. While Kurtz argues that humans can behave morally without relying on God, this text states that religion can also motivate good behavior. Furthermore, secular humanism emphasized by Kurtz relies on rationality, science, and technology as means to enhance human well-being, based on naturalism and disregarding the role of God. This text seeks to delve into Kurtz's views on secular humanism while exploring the debate on the role of religion in promoting good behavior. ABSTRAKTulisan ini membahas tentang konsep humanisme, teristimewa dalam konteks humanisme sekuler Paul Kurtz. Humanisme, sebagai gerakan yang berkembang selama masa Renaissance, menyoroti pentingnya kebahagiaan, kebebasan, dan hak asasi manusia. Kurtz, seorang tokoh penting dalam humanisme sekuler, mengartikulasikan pandangan hidup yang berfokus pada keberanian, kognisi, dan kepedulian sebagai kebajikan dasar yang mengarahkan kehidupan manusia. Kendati Kurtz berpendapat bahwa manusia dapat berperilaku baik tanpa perlu mengandalkan Tuhan, tulisan ini menyatakan bahwa agama juga dapat memotivasi perilaku baik. Selain itu, humanisme sekuler yang ditekankan oleh Kurtz, mengandalkan rasionalitas, ilmu pengetahuan, dan teknologi sebagai sarana untuk meningkatkan kesejahteraan manusia, dengan berlandaskan pada naturalisme dan mengesampingkan peran Tuhan. Tulisan ini berusaha menggali pandangan Kurtz tentang humanisme sekuler, sambil mengeksplorasi perdebatan tentang peran agama dalam mendorong perilaku baik.